Cardiac disease in pregnancy: still an arduous conundrum for the obstetrician - Marwah, Sheeba; Sharma, Manjula; Gaikwad, Harsha Shailesh; Mohindra, Ritin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Cardiac diseases, complicating about 1 percent of all pregnancies, account for significant maternal morbidity and mortality by being the leading cause of obstetrical intensive care unit admissions and of indirect maternal deaths. Of late, there has been observed a changing pattern in heart disease, the etiology having shifted from primarily rheumatic to predominantly congenital (75–82%), with shunt lesions preponderating (20–65%). Counseling and management of women of childbearing age with suspected cardiac disease ought to commence prior to conception; they should be managed by interdisciplinary teams; high risk patients must be treated in specialized facilities, and diagnostic procedures and interventions should be executed by mavens with profound expertise in the cardiovascular diseases and proficiency in treating pregnant women. This article provides a comprehensive review on management of cardiac disease in pregnancy to assist obstetricians in tackling this mystifying medical situation effortlessly, attaining a favorable feto-maternal outcome.